Evolution of the precursor structure during the preparation of the nanopowders with perovskite-type LnLn’O3 (Ln, Ln’ = REE) complex oxide phase in the La2O3-Lu2O3-Yb2O3 system - Oleksandr V. Shyrokov; Tatiana F. Lobunets; Olga V. Chudinovych; Tamara V. Tomila; Andrey V. Ragulya (Journal of Experimental Nanoscience)
The thermal decomposition of complex oxide phases, such as perovskite, in the La2O3-Lu2O3-Yb2O3 systemwith a specific surface area of 37 m2/g, synthesised by the heterogeneous precipitation method under non-isothermal conditions of linear heating at a rate of 5 deg/min, was studied to reveal the features of structure changes in intermediate products. Thermogravimetric and adsorption-structural analyses, infrared spectroscopy, powder diffraction and electron microscopy revealed that the decomposition of precursors occurs in two main stages. Up to 700 °C, the initial coordination spheres are destroyed in a sequential manner, resulting in the powders remaining amorphous in phase composition. However, with a gradual increase in the order of the atoms, the change in the pore structure is non-monotonic, with an inflection point observed at 450 and 675 °C. At 675 °C, the system undergoes a collapse, accompanied with decrease in both the pore volume (V∑) and the specific surface area (SBET), which attain the lowest values of 0.0415 cm3/g and 16.5 m2/g, respectively. The second stage of decomposition of the precursor in the temperature range of 750-825 °C is associated with the formation and accumulation of the crystalline phase of perovskite in the form of a nanodispersed mesoporous powder with a specific surface area of 18 m2/g and the average mesopore diameter of 17 nm corresponding to a particle size of 40 nm when using the calculated X-ray density of 8.26 g/cm3.